ASSOCIATION OF DIETARY HABITS WITH IRRITABLE BOWEL SYNDROME IN POPULATION OF DISTRICT KHAIRPUR MIRS, SINDH, PAKISTAN. : J Peop Univ Med Health Sci. 2025:15(2), 254-260. http://doi.org/10.46536/jpumhs/2025/15.02.648 - Safdar Ali Parvez Tunio1, Muhammad Siddique Rajput2, Amjad Ali Bhatti3, Farwa Batool4, Gotam Kumar2, Zeeshan Asad5 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Irritable Bowel Syndrome (IBS) is a prevalent functional gastrointestinal disorder characterized by chronic abdominal pain and altered bowel habits in the absence of detectable structural abnormalities. While dietary factors have been implicated in the pathophysiology of IBS, limited data exist regarding this association in rural populations of developing countries, including rural Sindh, Pakistan. OBJECTIVE: To assess the association between specific dietary habits and the prevalence of IBS among adults in rural Sindh, Pakistan. METHODS: A cross-sectional analytical study was conducted between February and August 2024 in three rural districts of Sindh province. A total of 850 individuals aged 18–60 years were recruited using multistage cluster sampling. The Rome IV criteria were used for IBS diagnosis. Dietary habits were assessed using a validated food frequency questionnaire (FFQ). Logistic regression was employed to determine associations, adjusting for confounders such as age, gender, physical activity, and socioeconomic status. RESULTS: Out of 850 participants, 176 (20.7%) were found to have IBS. High intake of spicy foods (AOR: 2.43; 95% CI: 1.62–3.64), low fiber intake (AOR: 1.89; 95% CI: 1.25– 2.86), frequent consumption of carbonated beverages (AOR: 2.14; 95% CI: 1.41–3.25), and irregular meal timings (AOR: 1.78; 95% CI: 1.12–2.82) were significantly associated with IBS. Protective dietary factors included daily consumption of vegetables (AOR: 0.56; 95% CI: 0.36 0.88) and probiotic-rich foods (AOR: 0.61; 95% CI: 0.39–0.94). CONCLUSION: Specific dietary habits, particularly those involving spicy and low-fiber foods, are significantly associated with IBS in rural Sindh. Dietary modification strategies should be integrated into the management and prevention frameworks for IBS in these communities.